Perspective: One-Cell and Cleavage-Stage Mouse Embryos Thrive in Hyperosmotic Oviductal Fluid Through Expression of a Glycine Neurotransmitter Transporter and a Glycine-Gated Chloride Channel: Clinical and Transgenerational Implications - Van Winkle, Lon J. (Frontiers in Physiology, 2020)
The osmolality of mouse oviductal fluid ranges from about 300 mOsmol/kg in the ampulla 0–3 h post coitus (h p.c.) to more than 350 mOsmol/kg in the isthmus 34–36 h p.c. Thus, it has been surprising to find that development of one-cell and cleavage-stage mouse embryos arrests in vitro in media exceeding 300 mOsmol/kg, and they develop best in unphysiological, hypotonic media. The glycine concentration in oviductal fluid can, however, rescue development in hypertonic media, so physiological conditions in vivo and in vitro likely work together to foster embryo well-being. Glycine acts on one-cell and cleavage-stage mouse embryos through the glycine-gated chloride channel, GLRA4, and uptake via the glycine neurotransmitter transporter, GLYT1. Since these processes lead to further signaling in neurons, the presence and function of such signaling in preimplantation embryos also should be investigated. The more we know about the interactions of physiological processes and conditions in vivo, the better we would be able to reproduce them in vitro. Such improvements in assisted reproductive technology (ART) could improve patient outcomes for IVF and potentially help prevent unwanted developmental abnormalities in early embryos, which might include undesirable epigenetic DNA and histone modifications. These epigenetic modifications may lead to transgenerational adult disorders such as metabolic syndrome and related conditions.